Uterine Perforation on Invasive Hydatidiform Mole during EMACO Treatment - Pradipta, Bram (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: Improving skill and knowledge to recognize and manage a rare case of uterine perforation on invasive hydatidiform mole. Method: Case report. Result: A 42 years old Indonesian woman, Parity 2 Abortus 2 with history of 2 c-sections and 2 curettage, came with chief complaint of recurrent vaginal bleeding since 4 months before admission. Patient had a history of previous curettage with indication of hydatidiform mole and recurrent bleeding with no histopathology results. On examination we found a vesicular mass with infiltration, destroying the right-front uterine corpus, size 8x6 cm with an internal echo mass. Chest x-ray showed multiple nodules in the lung. The patient, considered as low risk Gestational Trophoblastic Neoplasia patient with FIGO Score of 6, underwent chemotherapy with 2 series of methotrexate . Due to the non-declining level of -hCG, the regimen was added with EMACO. In the process of chemotherapy, the pa-tient’s-hCG declined but then she complained of major abdominal pain. Exploratory laparotomy was performed and we found a mass sized 5x5x5 cm on the right side of the uterus at the broad ligament with a rupture at the posterior part of the mass sized 0.5x0.5 cm. Upon incision of the uterus, we found a mass from the right side protruding to the isthmus of the uterus. Histopathology showed necrosis, blood and chorionic villi in myometrium corresponding to invasive mole. Patient was then given another 5 series of EMACO and her condition was unremarkable during the remaining course of treatment. Conclusion: Invasive mole treatment is determined based on the risk factors. Uterine perforation still occurred in this case regardless of the decreasing hCG level during EMACO treatment. It emphasizes the importance of clinical examination as chemotherapy responsiveness. Long-term treatment can have a good prognosis but good collaboration between the gynecologist and the patient is essential. [Indones J Obstet Gynecol 2014; 3: 162-165] Keywords: EMACO, invasive mole, perforation